No Reported Renal Stones with Intravenous Vitamin C Administration: A Prospective Case Series Study - Melissa Prier; Anitra C. Carr; Nicola Baillie (MDPI AG, 2018)
A few cases associating high dose intravenous vitamin C (IVC) administration with renal stone formation have been reported in the literature, however, no long-term studies investigating IVC administration and reported renal stones have been carried out. Our aim was to measure the frequency of reported renal stones in patients receiving IVC therapy. We carried out a prospective case series study of 157 adult patients who commenced IVC therapy at Integrated Health Options clinic between 1 September 2011 and 31 August 2012, with follow-up for 12 months. Inquiries into the occurrence of renal stones were conducted at enrolment, 6 and 12 months, and renal function blood tests were conducted at enrolment, 4 weeks and every 12 weeks thereafter in a subgroup of patients. No renal stones were reported by any patients in the study, despite 8% of the patients having a history of renal stones. In addition, the majority of patients investigated had stable renal function during the study period as evidenced by little change in serum creatinine levels and estimated glomerular filtration rate (eGFR) following IVC. In conclusion, IVC therapy was not associated with patient-reported renal stones. Although not the primary focus of this study, it was also observed that there was no significant change in mean serum creatinine or eGFR for those who had follow-up renal function blood tests.